Memory and emotions in antiquity - Kazantzidis, George 1979-; Spatharas, Dēmos 20./21. Jh (De Gruyter, 2024)
The contributions of this volume discuss the interfaces between memory and emotions in ancient literature, social life, and philosophy. They explore the ways in which memories intersect with emotions in the epics of Homer and Virgil, the importance of memory for the emotions scripts employed by public speakers to enhance the persuasiveness of their arguments, and 'cultural memory' in Philostratus' Heroicus. Contributions that focus on aspects of ancient societies and politics investigate memory and emotions in the Bacchic-Orphic gold leaves, the importance of memories on inscriptions commemorating private and public emotions, and the ways in which emotive memories enhanced the monumentalizing project of Herodes Atticus in Greece. The essays emphasizing philosophical approaches to memory and emotions discuss Aristotle's biological treatises and Augustine's deployment of nostalgia and autobiographical narrative in the wider frame of his didactic programme. Modern approaches to embodied cognition are also employed to shed light on how memories attached to our bodily experiences can enhance the interpretation of Roman literature
Keywords: Altertum; Altphilologie; Gedächtnis; Gefühl; Griechisch; Gefühl -- Motiv; Erinnerung -- Motiv; Latein; Literatur